Language and Identity in Multimodal Text: Case Study of Thailand’s Bank Pamphlet - Pruekchaikul, Korapat; Marques, Isabelle Simões (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2018)
With the main objective of presenting a linguistic model for the analysis of identity construction in multimodal texts, particularly in advertising, this article attempts to integrate three theoretical frameworks, namely the types of discourse of the Socio-Discursive Interactionism, Greimas’ actantial roles and the symbolic processes of the Grammar of Visual Design proposed by Kress & van Leeuwen. The first two theories are used to analyze verbal language form whereas the third is exclusively for images in advertising. The data sample is a Thai bank pamphlet of Siam Commercial Bank, collected in Bangkok, Thailand, in June, 2015. According to the data analysis, the theoretical frameworks employed here proves that identity, the psychological product, exists in the human mind and can be indexed by language in interaction. Also, the analysis found that identity could be projected as multimodally as language manifestation, of which forms are not only verbal but also pictorial.